PEMBERDAYAAN PEMUDA PALIMANAN MELALUI STRATEGI DAKWAH KOMUNITAS VESPA INDEPENDENT SARUNGAN (VIS) - Fiqih, Muhammad; Munawaroh, Mumun; Faoziyah, Sitti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Youth empowerment is one of the strategic efforts to strengthen the capacity of young people to become more active, productive, and engaged in socio-religious life. This study aims to describe the process of youth empowerment in Palimanan through da'wah strategies implemented by the Vespa Independent Sarungan (VIS) community. This community integrates culture, youth solidarity, and religious activities as a contextual approach to da'wah that is closely connected to the daily lives of young people. This research employed a qualitative approach using a case study method. Data were collected through observations, interviews, and documentation involving VIS community members and the surrounding community. The findings reveal that the VIS community implements its da'wah strategies through cultural approaches, social activities, and the reinforcement of Islamic values within Vespa community activities. This approach successfully attracts young people to actively participate in positive activities while fostering an inclusive religious identity without diminishing creativity and togetherness. Furthermore, the empowerment initiatives carried out by the VIS community have generated positive impacts, including increased religious awareness, strengthened social solidarity, and a reduction in negative activities among youth. Therefore, this community-based da'wah strategy can serve as an alternative model for youth empowerment in local communities.